Motivation of paid peer mentors and unpaid peer helpers in higher education - Jenepher Lennox; Dominique Leonard (International Journal of Evidence Based Coaching and Mentoring, 2010)
While considerable research supports the use of peer mentoring to improve academic performance and decrease student attrition, few studies have examined the motives of peer mentors to take on this role and less clear are distinctions in peer mentor motivation in paid versus unpaid settings. Using semi-structured interviews, this study explored the motivations of student peer mentors in voluntary and paid peer mentoring services at the University of Ottawa, Canada. The findings showed that both paid and unpaid mentors reported being motivated by self-oriented reasons, such as learning about themselves and fulfillment, but that paid mentors were primarily motivated by generativity, or the desire to help young people, while volunteer peer helpers reported being highly motivated to fulfill social needs. This research helps shed light on the impact of payment on motivation to perform the mentoring function and on the communication strategies which may be used to attract student mentors to this position.